EVALUATION OF COMMERCIALLY-AVAILABLE COMPUTERIZED COGNITIVE TRAINING PROGRAMS AMONG OLDER ADULTS. (11th November 2018) - Tetlow, A; Edwards, J
Abstract: The number of commercially-available computerized cognitive training programs aimed at countering age-related cognitive decline has rapidly expanded over the past decade. Some researchers have questioned the efficacy of such programs. This systemic literature review and meta-analysis evaluated the efficacy of commercially available, cognitive training programs. We examined the effects of such programs to improve cognitive and everyday function. Randomized clinical trials of commercially available computerized cognitive training programs including samples of adults aged 55 and older who were free from health conditions known to impact cognition were included in analyses (N=21 studies). All included studies were evaluated for any potential bias using the PEDro scale (M=7.22, SD=1.44). Using random effects models, effect sizes were calculated to evaluate the efficacy of cognitive training to improve cognitive domains such as attention, executive function, memory, processing speed, reasoning, verbal fluency, visuospatial memory, and everyday function. Results indicated small to medium effects for improved cognitive performance in the domains of attention (d = 0.651, p = .002), processing speed, (d = 0.294, p = .002), and visuospatial memory, (d = 0.252, p < .016). Additionally, there was far transfer to improved everyday function (d = 0.277, p < .001). These findings show that commercially available computerized cognitive training programs have the ability to improve certain cognitive abilities. Furthermore, the results show that these programs may also enhance everyday function. Commercially available cognitive training can enhance older adults' cognitive abilities, and generalize to real-world function.